Preysler polyoxometalate supported on functionalized graphene oxide nanoparticles: synthesis, identification and investigation of its catalytic activity - Ali Javid (مواد نوین, 2024)
Abstract Introduction: In the last two decades, nanoparticles obtained from graphene oxide (GO) have been of great interest to researchers in various sciences, including chemistry. Also, the functionalization of graphene oxide can improve its functional properties. In industrial chemistry, one of the most important applications of functionalized graphene oxide is its use as a catalyst. Methods: In this project, after preparing graphene oxide nanoparticles, they were grafted by functionalized polyamine (GO-NH2), and then by Preissler's heteropolyacid (Pr@GO-NH2). Preysler is one of the types of polyoxometalate clusters, which has unique characteristics and is used as a Lewis acid catalyst due to having a large number of acidic protons. The structure of these new nanoparticles was investigated by spectral methods such as XRD, FTIR, SEM, TEM, EDX and TGA. Also, after preparing Pr@GO-NH2, its catalytic activity was measured in the reaction of producing oxime from aldehyde and hydroxylamine. Findings: By using the mentioned spectral methods and comparing some spectra of Pr@GO-NH2 with GO-NH2 and GO, the structure of Pr@GO-NH2 nanoparticles was identified and confirmed. Also, the preparation of oxime in the presence of these nanoparticles confirmed its high catalytic activity. Based on the obtained results, this reaction was carried out in the presence of 0.03 grams of catalyst at 50°C for 30 minutes and in the presence of water as an environmentally friendly solvent.